Design and application of a rapid cooling device for burn injuries in pre-hospital first aid (一种战现场烧伤用创伤面降温装置的设计与使用方法) - ZENG Zihuan (曾子桓); YAO Xi (姚喜); Chen Kun (陈堃); TIAN Huilin (田慧玲); SHEN Ruixue (史雯欣); WANG Zonghua (沈瑞雪); (王宗华) (Association of Integrative Nursing, 2022)
Aiming at the requirements of rapid cooling of the burned site in early first-aid treatment of burns, our research team designed a device for cooling the wound surface of burns. To meet the purpose of reducing of wound temperature, swelling and seepage rapidly, the device which uses the principle of urea and water mixed reaction refrigeration consisted of the adsorption of shell, water storage bag, bag and cover body. The device, portable and easy to operate, can withstand high temperature UV rays. It is up to the mustard for outdoor environments lacking water sources such as field battles. At the same time, it reduces the possibility of secondary wounds caused by chemical residues in traditional cooling therapy. (本研究设计了一款烧伤用创伤面降温装置, 运用尿素与水混合反应制冷的原理, 通过吸附壳体、蓄水袋、收容袋和盖体的配合使用以达到迅速降低创面温度, 减少创面肿胀渗液等目的。该装置轻便易于携带, 能耐受高温和紫外线, 适合野战现场等缺乏水源的户外环境, 且简单易操作, 能有效避免创面二次损伤。)